USING OF SOME THERMODYNAMIC PARAMETERS OF NANO AND ORDINARY ZINC ADSORPTION IN DESERT SOIL - Akram A. H. Al-Hadethi,; Ahmed F. M. Al-Enzy, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A laboratory experiment was carried out to study the ability of soil to adsorption of Zinc added from three sources: nano-Zinc oxide (ZnnO), nano-chelated Zinc (Znn-DTPA), and nano-organic Zinc (Znn-HA), with several concentrations ranging from 0-160 mg Zn kg-1. Zinc was added for each concentration at an amount of 20 ml per 1 gm of soil. As for the ordinary sources, Zinc was added from the ordinary sources, Zinc oxide, ZnO, chelated Zinc , Zn-DTPA, and ordinary organic Zinc , Zn-HA, in several concentrations, ranging from 0-500 mg Zn kg-1. Each concentration was added at 20 ml per 1 gm of soil and two repetitions for each source. The adsorption capacity of the soil and the binding energy of the adsorbed Zinc , and to estimate the thermodynamic parameters for the adsorption of nano-Zinc in desert soils, and Freundlich equations were used to study and evaluate the adsorption process. The thermodynamic parameters Kº, ΔGº, ΔHº, and ΔSº were calculated based on the results of the adsorption experiment. The results of the experiment indicate that both equations succeeded in describing the adsorption of nano and ordinary Zinc depending on the value of the determination coefficient of (R2), which ranged between (0.959 - 0.971) and (0.884 - 0.985) for each of the Langmuir and Freundlich equations respectively. As for the thermodynamic equilibrium constant Kº, it decreased with the increase in the reaction temperature for three sources: Znn-DTPA, ZnO, and Zn-HA, while it increased with the other three sources. The negative ΔGº values for all sources of nano and ordinary Zinc parameters spontaneity of the reaction at both temperatures 25°C - 45°C.